Analisis Dampak Implementasi Belt And Road Initiative Terhadap Sektor Perekonomian Vietnam Tahun 2017 - 2022 - Aprilion, Audi; Wijayati, Hasna; Widhiyoga, Ganjar (Kajian Hubungan Internasional, 2024)
The Belt and Road Initiative (BRI) projects initiated by China since 2013 have been implemented in various countries in Europe, Africa, and Asia, where there are BRI corridors passing through these continents, including Vietnam. The purpose of this research is to assess the impact of the BRI on Vietnam's economy by examining tangible benefits for the Vietnamese people. The methods employed in this study include Geopolitics and international cooperation, which are highly evident in the BRI project processes. The results of this research indicate that Vietnam indeed requires investment to develop its insufficient infrastructure facilities. Moreover, based on the collected data, Vietnam needs substantial investment funds for infrastructure development. With the implementation of BRI in Vietnam, it will make it easier for Chinese investment funds to enter. Therefore, the BRI plays a crucial role in facilitating Vietnam's infrastructure development by providing investment funds. In this study, the relationship between infrastructure development, China's motives in the BRI, and the economic growth of Vietnam will be discussed in the context of this research. Keywords: BRI, Vietnam, China, economy, infrastructure